1986
DOI: 10.3109/00365598609040555
|View full text |Cite
|
Sign up to set email alerts
|

Some Clinical Aspects of Uroflowmetry in Elderly Males:A Population Survey

Abstract: A random sample of 200 males aged 50 years or more was selected from the National Register in order to investigate various aspects of spontaneous uroflowmetry and to estimate the frequency of prostatism and symptoms of lower urinary tract dysfunction. All in all the data from 112 persons were analysed. The prevalence of prostatism was found to be 17% (95% confidence limits 11-26%), while 88% (95% confidence limits 83-95%) experienced various degrees of symptoms. Only few associations between single symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Max flow rate has been shown to be significantly associated with symptom scores in some studies [14, 15], while other investigations have shown only weak correlations [4, 16]. In these latter studies, a clear distinction was shown between QoL and storage symptoms on the one hand and objective data and voiding symptoms on the other.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Max flow rate has been shown to be significantly associated with symptom scores in some studies [14, 15], while other investigations have shown only weak correlations [4, 16]. In these latter studies, a clear distinction was shown between QoL and storage symptoms on the one hand and objective data and voiding symptoms on the other.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, free-flow evaluation alone does not allow to discriminate bladder outlet obstruction from impaired detrusor contractility [3]. These limitations notwithstanding, uroflowmetry has in recent years gained a relevant role in the evaluation of LUTS, owing to its noninvasiveness, rapidity, and simplicity of execution [4]. In this paper, we describe the uroflowmetry data of a selected number of QUIBUS (QUality of life Investigated in BPH patients with Urinary Symptoms) patients (n = 366) and their relationships with age, prostate volume, and the IPSS and ICS-BPH scores.…”
Section: Introductionmentioning
confidence: 99%
“…However, those two studies had different definitions of treatment success-the former strictly defined success as 50% improvement in IPSS, Qmax, and PVR [ 19 ], whereas the latter defined it as fair, good, or excellent on a subjective satisfaction scale (full scale: poor/fair/good/excellent) [ 19 ]. It is already known that UFM parameters and voiding symptoms are not well correlated [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that symptom severity and prostate size are minimally correlated [32, 33, 34, 35]. However, recent community studies have suggested stronger relationships that are comparable to correlations found in other disease areas, where relationships are well accepted [3, 12].…”
Section: Introductionmentioning
confidence: 99%